Modulation of urban atmospheric electric field measurements with the wind direction in Lisbon (Portugal) - Silva, Hugo (2015)
Atmospheric electric field measurements (potential gradient, PG) were retrieved in the urban environment of the city of Lisbon (Portugal). The measurements were performed with a Benndorf electrograph at the Portela Meteorological station in the suburbs of the city (NE from the centre). The period of 1980 to 1990 is considered here. According to wind direction, different content and types of ions and aerosols arrive at the measurement site causing significant variations to the PG. To the south there are significant pollution sources while to the north such sources are scarcer . The Iberian Peninsula is found east of the station and the Atlantic Ocean covers the western sector, Wind directions are divided in four sectors: i) NW: 270º ≤ θ ≤ 360º; ii) NE: 0 ≤ θ ≤ 90º; iii) SE: 90 ≤ θ ≤ 180º; iv) SW: 180º ≤ θ ≤ 270º. Analysis of weekly cycle, caused by anthropogenic pollution related with urban activity, was undertaken for each wind sector. NW sector has been shown to be less affected by this cycle, which is attributed to the effect of marine air. The daily variation of NE sector for weekends reveals a similar behaviour to the Carnegie curve, which corresponds to a clean air daily variation of PG, following universal time, independent of measurement site.